Phenotypic Character of Eight Mango Varieties (Mangifera indica L.) Collected by Purwodadi Botanic Garden - Rindyastuti, Ridesti; Goni, Abdul (Proceeding International Conference on Global Resource Conservation, 2013)
Mango is a tropical fruit plant. Distribution center of mango species in Indonesia are in Sumatra and Borneo. Among the species, Mangifera indica L. has more varieties than most other species. Eight varieties of M. indica L. which are Blenyik Bulat, Wader, Bapang, Gondo Lumut, Madu, Endog, Gandik Luyung and Krasak Candi has been studied to recognize the phenotypic character of superior germplasm of mango varieties. Qualitative and quantitative characters of varieties have been measured. Varieties of Madu, Endog and Krasak Candi has a sweet fruit flavor and relatively non-fibrous with the highest scoring value 14 and 12. Quantitatively, it is known that the size of mango varieties under study pertained small, range from 0.12 to 0.3 kg. However, Blenyik Bulat variety with very small fruit has a very attractive appearance, yellow when it is ripe with a uniform color. Based on the ratio between the weight of fruit peel and seeds, it is known that the varieties have thick flesh, heavy pieces of meat more than 60%, variety Blenyik Bulat 80%, Wader 67%, Madu 73%, Bapang 96%, Gondo Lumut 96%, 94% Endog, Gandik Luyung 93%, 89% Krasak Candi. From phenotypic characters of mango variety, we can conclude that the variety of Madu, Endog, and Krasak Candi are quite excellent and their fruit can be developed for domestic consumption, as they have sweet taste. While for other varieties such as Blenyik Bulat, Gondo Lumut, and Bapang, can be developed for processing fruit as juice or dessert even can be developed for export consumption for example to Europe and Australia, as they have sour taste. Keyword: Manggo, Character, Phenotypic.